A historical overview of financial crises in the United States - Shachmurove, Yochanan (Economics and Business Review, 2011)
One of the few constants since the United States declared its independence is the presence of frequent financial crises with similar causes. In the nineteenth century, these panics were frequent with eight occurring over the century. However, following the Second World War there was a period of relative calm, which may have led to complacency. The Savings and Loans and the current financial crises have shown that these events remain a very real threat to economic stability. I have greatly benefitted from research assistance by Zach Winston from Pennsylvania State University and Gregory Kauffman from the University of Pennsylvania. (original abstract)